Desert Royal - Sasson, Jean (London Bantam Books, 2000)
In Princess, readers were shocked by Sultana's revelations about life in Saudi Arabia's royal family. Royal women live as virtual prisoners, surrounded by unimaginable wealth and luxury, privileged beyond belief, and yet subject to every whim of their husbands, fathers, and even their sons. Daughters of Arabia featured Sultana's teenage daughters, determined to rebel but in very different ways. And now, in Desert Royal, Sultana's fight for women's rights in a repressive, fundamentalist Islamic society, has an extra sense of urgency. The threat of world terrorism, the gathering strength of religious leaders and the discontent of impoverished Saudis are threatening to topple the comfortable world Sultana has known. But an extended family 'camping' trip in the desert brings Sultana and her relatives face to face with their nomadic roots, and nourishes her will to carry on the fight for women's rights in all Muslim countries. This updated edition contains an all-new chapter as well as a letter from Sultana herself, encouraging all women to take up the struggle for freedom for their abused sisters throughout the world.
Keywords: Women--Social Conditions -- Saudi Arabia -- Princesses